An empirical study on the determinants of an investor's decision in unit trust investment - Sanmugam Annamalah; Murali Raman; Govindan Marthandan; Aravindan Kalisri Logeswaran (Economies, 2019)
Unit trust is a convenient way of investing and a sensible way to build one's wealth in the medium term and subsequently in the long-term. Investment specialists will manage the investments and spread the risks through careful diversification. The basic nature of the unit trust is that it carries a low-level of risks and accordingly determines a lower level of returns compared to other financial instruments. There is a lack of research that empirically investigates the factors that influence an investor's decision in unit trust investment, particularly in a Malaysian setting. The purpose of this study is to analyse the factors that influence an investor's investment decision in purchasing a unit trust. This paper aims to narrow this research gap, whereby financial status, risk taking behaviour, investment revenue and related information are hypothesized to exert statistically significant influences on the investor's decision in unit trust investment. The empirical study uses a quantitative research approach whereby survey data have been sampled from 202 participants using a convenient sampling technique. This research is cross-sectional and uses primary data for analysis. Data analysis has been carried out using multiple regression analysis. The empirical research finds that financial status, risk taking behaviour, and sources of information significantly influence the investors' investment behaviours in unit trusts. However, there was not enough evidence to support the claims that investment return and revenue have a statistical relationship to the investors investment behaviours regarding unit trusts. The findings from this research will have huge implications for investors and for financial institutions. This paper helps fund managers and brokers to understand the behaviours of an individual investor in response to a unit trust. On the other hand, this helps them to better target their customers, and persuade customers to make their investments in a unit trust effectively and efficiently, thereby helping them to manage their financial wealth with less risk but better future prospects.
Keywords: K25; O16; 330; financial instrument; financial status; investment; investment revenue; mutual fund; risk behaviour; sources of information; unit trust